Adlerian psychotherapy - Carlson, Jon; Englar-Carlson, Matt (Theories of psychotherapy series., 2017)
This book provides an introduction and overview to Alfred Adler's person-centered approach to psychotherapy. In Adler's view, all behavior has social meaning, and the socio-cultural context of a person's life is a driving influence on their mental health and life experiences.